The BULT Method for Pediatric Minilaparoscopic Pyeloplasty in Infants: Technique and Results - Ludwikowski, Barbara Magda; Botländer, Michael; González, Ricardo (Frontiers in Pediatrics, 2016)
We reviewed retrospectively the results of transperitoneal minilaparoscopic pyeloplasty in children younger than 2 years. The surgical technique utilized as well as the retrograde placement of the stent is described in detail. Twenty-four consecutive children with a mean age of 7.9 months (range 1–23), a mean weight of 7.4 kg (range 4–12), and a mean follow-up of 18 months (range 3–59) are included. Preoperative grade of dilatation was 3.8 (SFU scale) and postoperatively improved to 1.5. The AP diameter of the pelvis decreased from a mean of 28–9 mm. In 83% of cases, there was complete resolution of hydronephrosis (grades 0–2) and the rest showed improvement. There was one conversion to open surgery in a child with a horseshoe kidney. There was one omental prolapse though a port site in a child in whom an inappropriate drain was used. There were no stent-related complications and no reinterventions for persistent or recurrent obstruction. Given these outcomes, low complication rate and excellent cosmetic results, we recommend transperitoneal minilaparoscopy with a double J stent and a perirenal drain for infants requiring pyeloplasty.